Factor Structure of the Torrance Tests of Creative Thinking Figural Form B in Spanish-Speaking Children: Measurement Invariance Across Gender - Krumm, Gabriela Liliana (2014)
On the basis of contradictory findings regarding the factor structure of the Torrance Tests of Creative Thinking (TTCT) Figural scale, the objective of this study was to compare, through a confirmatory factor analysis (CFA), four theoretical models that explain the operationalized creativity construct with the TTCT. We evaluated a sample of 577 Spanish-speaking school children of both genders, aged 9 to 14 years. The CFA of most satisfactory fit identified two correlated factors: (a) innovative and (b) adaptive. Besides, multigroup CFA revealed that the 2-factor solution was invariant (configural, metric, and structural) across gender. Finally, MANOVAs were conducted to analyze the differences in each factor and subscale according to gender, revealing significant group differences. The methodological and educational implications of the results are discussed.